Feeding habits of Chondrichthian Mustelus Mustelus - Smoothhound : Triakidae- in Syrian marine water - Ali, Malek Fares; Saad, Adib Saad; Kurbaj, Haitham Kurbaj (Iraqi Journal of Aquaculture, 2022)
This study was performed on the smoothhound shark: Mustelus mustelus (Linnaeus, 1758), during the period between December 2005 and April 2009, in the Eastern Levant along the Syrian coast. A total of 222 specimens examined (143 females, 79 males) discerned: The monthly sampling showed: the Smoothhound shark, M. mustelus were normally caught throughout the year, mainly in spring and summer, at fishing sites from Raas Albassit to Tartus city (34º. 40΄and 35º.80΄ N, 35º.70΄and 36º.05΄ E) of the Syrian coast, from shallow water to depth 250 m. The coefficient of void of total specimens stomachs was high (C.V=61.7 %), values were almost equal between males and females, the higher value recorded for adult females (C.V =62.5 %). The prey items belong to three collections: (Bony fish, Crustaceans, and Mollusks), bony fish occupy the first position for: Coefficient of feeding (Q=1560.4), Frequency of prey index (91.8 %), Gravimetric percentage of prey index (C.P=38.6 %). Crustaceans came in the first position for Numerical Percentage of Prey Index (C.N=45.6 %).